Making, Buying, and Concurrent Sourcing: Implications for Operating Leverage and Stock Beta - Lambrecht, Bart M.; Pawlina, Grzegorz; Teixeira, João C. A. (Review of Finance, 2016)
Abstract We present a real options model of a firm’s make-or-buy decision under demand uncertainty. “Making” is subject to decreasing returns to scale, fixed costs, and capital investment. “Buying” happens at a fixed price and requires no investment. Three distinct procurement regimes endogenously arise: buying, making, or concurrent sourcing for, respectively, low, intermediate, and high demand. Capital constraints encourage buying or concurrent sourcing. Operating leverage peaks when the firm switches between buying and making, and it is lowest (and negative) at the switch between making and concurrent sourcing. This non-monotonic pattern mirrors and drives the behavior of the firm’s beta.